Kepemimpinan kepala sekolah di era pandemi - Syahril Syahril; Sulastri Sulastri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims to determine the effectiveness of school principal leadership in the era of the co-19 pandemic. This type of research is descriptive research. The population of this study were 334 public junior high school teachers in the city of Sungaipuh with PNS status. Sampling was carried out using a stratified proportional random sampling technique. The size of the sample was obtained by 98 people. The instrument used to collect data in this study was a Likert scale model questionnaire, the data was processed using the mean and percentage formulas. The results showed that the leadership of school principals in the era of the Covid-19 pandemic was seen based on indicators: (a) influencing teachers was in the moderate category (77.31%); (b) moving teachers is in the medium category (78.95%); (c) directing teachers to be in the medium category (75.81%); (d) motivating teachers in the high category (83.79%); and (e) guiding teachers in the moderate category (73.86%). So, the leadership of the school principal at Sungai Full City Public Middle School during the pandemic era was in the moderate category with a percentage of 77.95%.